2022
DOI: 10.1111/vop.12995
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal susceptibility ofFusariumspecies andAspergillus fumigatuscultured from eleven horses with fungal keratitis

Abstract: To examine the relationship between Minimum Inhibitory Concentration (MICs) and response to therapy of 6 Fusarium spp. and 5 Aspergillus fumigatus isolated from equine ulcerative keratitis cases. Procedure: Fungi were identified by morphology and Internal Transcribed Spacer (ITS) polymerase chain reaction (PCR) with sequencing and evaluated at the University of Texas Fungal Testing Laboratory for susceptibility to three azole antifungals (miconazole, voriconazole, posaconazole), natamycin, and two echinocandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The results also showed the presence of mutations TR46/Y121F/T289A (n = 17), TR34/L98H (n = 1), and TR53 (n = 1) and one isolate had a wild-type CYP51 sequence. Thus, there was evidence of the need to implement agricultural surveillance and monitoring of antifungal resistance in isolates from animals and humans [104], in addition to the research for resistant environmental strains, and the evaluation of pesticide uses in floriculture, agriculture, and livestock systems [74,97,98,105]. In the specific case of aqueous media, some studies have reported that filamentous fungi and yeasts, after passing through municipal treatment plants, can acquire resistance to one or several antifungals [58,99,101].…”
Section: Susceptibility Resistance To Antifungals and Resistant Fungi...mentioning
confidence: 99%
“…The results also showed the presence of mutations TR46/Y121F/T289A (n = 17), TR34/L98H (n = 1), and TR53 (n = 1) and one isolate had a wild-type CYP51 sequence. Thus, there was evidence of the need to implement agricultural surveillance and monitoring of antifungal resistance in isolates from animals and humans [104], in addition to the research for resistant environmental strains, and the evaluation of pesticide uses in floriculture, agriculture, and livestock systems [74,97,98,105]. In the specific case of aqueous media, some studies have reported that filamentous fungi and yeasts, after passing through municipal treatment plants, can acquire resistance to one or several antifungals [58,99,101].…”
Section: Susceptibility Resistance To Antifungals and Resistant Fungi...mentioning
confidence: 99%
“…Once considered a rare opportunistic infection, FK now accounts for 6-53 % of all infectious ulcerations in humans and 20-57 % of infectious ulcerations in horses, the most affected veterinary species [9][10][11][12]. This escalation in FK incidence, attributed to factors such as environmental change and a growing population of immunosuppressed individuals, is paralleled by concerning development of resistance among the causative organisms to the limited arsenal of available antifungal agents [3,[12][13][14][15]. Antifungal resistance is especially common in species of Fusarium [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This escalation in FK incidence, attributed to factors such as environmental change and a growing population of immunosuppressed individuals, is paralleled by concerning development of resistance among the causative organisms to the limited arsenal of available antifungal agents [3,[12][13][14][15]. Antifungal resistance is especially common in species of Fusarium [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These results, however, are notoriously challenging to interpret, particularly in the absence of established drug breakpoints for most Aspergillus and Fusarium species [12]. In vitro resistance in the face of clinical efficacy, and vice versa, are both regularly reported [8,13,14]. A driving factor of this incongruity is that traditional MIC assays exclusively test antifungals against a suspension of asexual fungal spores called conidia [11].…”
Section: Introductionmentioning
confidence: 99%